Effect of wettability heterogeneity and reservoir temperature on CO2 storage efficiency in deep saline aquifers - Al-Khdheeawi, E.; Vialle, Stephanie; Barifcani, Ahmed; Sarmadivaleh, Mohammad; Iglauer, Stefan (Elsevier, 2018)
Reservoir heterogeneity at various length scales is a well-established fact. This includes reservoir wettability - a key factor influencing CO 2 geo-storage efficiency and containment security - which changes with depth, and is generally non-uniform due to different depositional environments and fluid flow paths over geological times. However, the effect of heterogeneous wettability distribution on CO 2 storage efficiency is not understood. Moreover, there is a knowledge gap in terms of how temperature affects capillary and dissolution trapping, CO 2 mobility and vertical CO 2 migration distance, particularly when coupled with wettability heterogeneity effects. Thus, in this work we studied the effect of wettability heterogeneity and reservoir temperature on the vertical CO 2 plume migration, and capillary and dissolution trapping capacities. Our results clearly show that both wettability heterogeneity and reservoir temperature have a significant effect on vertical CO 2 migration, and the associated capillary and dissolution trapping mechanisms: both heterogeneously distributed wettability and higher temperature significantly accelerated the vertical CO 2 migration, CO 2 mobility and solubility trapping, while it reduced residual trapping. We thus conclude that wettability heterogeneity and reservoir temperature are important factors in the context of CO 2 geo-storage, and that heterogeneous wettability and higher reservoir temperatures reduce storage capacity.